The influence of exothermic reactions on the nonequilibrium level of discharge plasma - Chernyak, V.Ya.; Iukhymenko, V.V.; Prysiazhnevych, I.V.; Martysh, Eu.V. (Вопросы атомной науки и техники, 2013)
The comparative analysis of plasma parameters of transverse arc and discharge in the gas channel with liquid wall was made for different working gas and liquids (for air, distilled water and for its mixtures with ethanol). Electronic excitation temperatures Te* of atoms, vibrational Tv* and rotational Tr* temperatures of molecules in the generated plasma were determined by optical emission spectroscopy. It was shown that both discharges generate nonequilibrium plasma in the case of working gas air and working liquid – distilled water. Adding a fuel (ethanol) into the plasma system with O2 leads to the increasing of rotational and vibrational temperatures of molecules, which became equal to each other within the errors. This may indicate that the exothermic reactions reduce the level of nonthermality of the generated plasma as a result of additional energy supply for heavy components in the process of complete combustion of hydrocarbons. Порівняльний аналіз параметрів плазми поперечної дуги та розряду в газовому каналі з рідкою стінкою проведений для різних робочих газів та рідин (для повітря, дистильовоної води та їх суміші з етанолом). Електронні температури заселення Te* атомів, коливальна Tv* і обертальна Tr* температури заселення молекул у плазмі, що генерується, визначені за допомогою оптичної емісійної спектроскопії. Показано, що обидва розряди генерують нерівноважну плазму у випадку робочого газу – повітря та робочої рідини – дистильованої води. Додавання палива (етанолу) в плазмову систему призводить до збільшення обертальної та коливальної температур заселення молекул, які стають рівними одна одній у межах похибки. Це може свідчити про те, що екзотермічні реакції зменшують рівень нерівноважності плазми, що генерується, внаслідок подачі додаткової енергії важкій компоненті в процесі повного згорання вуглеводнів. Сравнительный анализ параметров плазмы поперечной дуги и разряда в газовом канале с жидкой стенкой проведен для различных рабочих газов и жидкостей (для воздуха, дистиллированной воды и их смеси с этанолом). Электронные температуры заселения Te* атомов, колебательная Tv* и вращательная Tr* температуры заселения молекул в генерируемой плазме определены с помощью оптической эмиссионной спектроскопии. Показано, что оба разряда генерируют неравновесную плазму в случае рабочего газа – воздуха, и рабочей жидкости – дистиллированной воды. Добавление топлива (этанола) в плазменную систему приводит к увеличению вращательной и колебательной температур заселения молекул, которые становятся равными друг другу в пределах погрешности. Это может свидетельствовать о том, что экзотермические реакции уменьшают уровень неравновесности генерируемой плазмы в результате подачи дополнительной энергии тяжелой компоненте в процессе полного сгорания углеводородов.